Expanding the phenotype of mucopolysaccharidosis type II retinopathy. (3rd September 2021) - Kowalski, Tanya; Ruddle, Jonathan B; de Jong, Gerard; Mack, Heather G
ABSTRACT: Purpose : To report novel retinal findings in two male patients with mucopolysaccharidosis type II (Hunter syndrome) receiving long-term human recombinant idursulfase enzyme replacement therapy.Method : Two males aged 19 and 26 years who had received enzyme replacement therapy for 12 and 13 years, respectively, with good compliance and no infusion-related reactions, were examined clinically and underwent optical coherence tomographic scanning of the retina and electroretinography testing.Results : Case 1 had visual acuity 20/32 in each eye and case 2 had visual acuity 20/25 in each eye. Both patients had clinically unremarkable anterior segment and fundus examinations. Ocular coherence tomography imaging in both patients showed thickening of the external limiting membrane with hyperreflective material in at least one eye each. One patient had bilateral foveoschisis and the other had mild foveal hypoplasia. Electroretinography showed a negative response in the patient with foveoschisis and reduced amplitudes in the patient with foveal hypoplasia.Conclusions : These two patients with Hunter syndrome receiving idursulfase treatment both have subfoveal deposition of hyperreflective material in the external limiting membrane despite good compliance and tolerance of the standard dose of enzyme therapy for this disorder. One patient has developed foveoschisis and negative electroretinogram suggesting abnormality of inner retinal function. Further studies are needed to determine the nature of the hyperreflective material, as well as the effect of systemic treatment on retinal findings in patients with mucopolysaccharidosis type II.